PENGARUH INTELLECTUAL CAPITAL TERHADAP FINANCIAL PERFORMANCE (Studi Pada Perusahaan Sub Sektor Property dan Real Estate yang Terdaftar di Bursa Efek Indonesia (BEI) Tahun 2014-2016) - Siti Barokah; Wilopo Wilopo; Inggang Perwangsa Nuralam (Jurnal Administrasi Bisnis, 2018)
This study aims to identify and analyze the influence intellectual capital to the financial performance. This type of research is explanatory research with a quantitative approach. Variabel examined included intellectual capital is created by capital employed (Value Added Capital Employed - VACA), human capital (Value Added Human Capital - VAHU), and structural capital (Structural Capital Value Added - STVA), and financial performance measured by return on assets (ROA). The study population was the property and real estate sub sector companies listed. The sample is this research totalled 34 companies obtained from sampling purposive sampling. This type of data used is an secondary data. The technique of data collection was done with the methods documentation. Analysis of the data used in the form of descriptive, classic assumption test, and multiple linear regression analysis. The research finding indicate that the VACA, VAHU, and STVA variables are simultaneously affected on ROA. The finding partially indicate VACA, VAHU, and STVA effest significantly to Return On Assets (ROA). Keywords : Intellectual Capital, Value Added Capital Employed (VACA), Value Added Human Capital (VAHU), Structural Capital Value Added (STVA), Return On Assets (ROA) ABSTRAK Penelitian ini bertujuan untuk mengetahui dan menganalisis pengaruh intellectual capital terhadap financial performance. Jenis penelitian ini yang digunakan adalah explanatory research dengan pendekatan kuantitatif. Variabel yang diteliti meliputi intellectual capital yang diciptakan dari penjumlahan capital employed (Value Added Capital Employed - VACA), human capital (Value Added Human Capital - VAHU), dan structural capital (Structural Capital Value Added - STVA), serta financial performance perusahaan, yaitu return on assets (ROA). Populasi penelitian ini adalah perusahaan sub sektor property dan real estate yang terdaftar di Bursa Efek Indonesia (BEI). Sampel dalam penelitian ini berjumlah 34 perusahaan diperoleh dari metode purposive sampling. Jenis data yang digunakan adalah data sekunder dan teknik pengumpulan data dilakukan dengan metode dokumentasi. Analisis data yang digunakan berupa statistik deskriptif, uji asumsi klasik, dan analisis regresi linier berganda. Hasil penelitian menunjukan VACA, VAHU, dan STVA secara bersama-sama berpengaruh signifikan terhadap ROA. Secara parsial menunjukan bahwa VACA, VAHU, dan STVA berpengaruh signifikan terhadap ROA. Kata Kunci : Intellectual Capital, Value Added Capital Employed (VACA), Value Added Human Capital (VAHU), Structural Capital Value Added (STVA), Return On Assets (ROA)